Entrevista com Barry Friedman - Arguelhes, Diego Werneck; Pereira, Jane Reis Gonçalves (Revista Publicum, 2018)
Entrevista realizada com o Prof. Barry Friedman, Jacob D. Fuchsberg Professor of Law and Affiliated Professor of Politics, New York University (NYU)